Chloride Accumulation in Mammalian Olfactory Sensory Neurons - Kaneko, Hiroshi; Frings, Stephan (The journal of neuroscience, 2004)
The generation of an excitatory receptor current in mammalian olfactory sensory neurons (OSNs) involves the sequential activation of two distinct types of ion channels: cAMP-gated Ca2+-permeable cation channels and Ca2+-gated Cl- channels, which conduct a depolarizing Cl- efflux. This unusual transduction mechanism requires an outward-directed driving force for Cl-, established by active accumulation of Cl- within the lumen of the sensory cilia. We used two-photon fluorescence lifetime imaging microscopy of the Cl--sensitive dye 6-methoxy-quinolyl acetoethyl ester to measure the intracellular Cl- concentration in dendritic knobs of OSNs from mice and rats. We found a uniform intracellular Cl- concentration in the range of 40-50 mm, which is indicative of active Cl- accumulation. Functional assays and PCR experiments revealed that NKCC1-mediated Cl- uptake through the apical membrane counteracts Cl- depletion in the sensory cilia, and thus maintains the responsiveness of OSNs to odor stimulation. To permit Cl- accumulation, OSNs avoid the “chloride switch”: they do not express KCC2, the main Cl- extrusion cotransporter operating in neurons of the adult CNS. Cl- accumulation provides OSNs with the driving force for the depolarizing Cl- current that is the basis of the low-noise receptor current in these neurons.